Allelopathic effects of parthenium weed debris in soil on the emergence and development of rice - O. Biswas, K.P. Paul; S. Ghosh; S.M. Rezaul Karim (2010)
An investigation was made to assess the allelopathic effects of parthenium weed debris ( Parthenium hysterophorus L.) on the emergence and seedling development of rice. Parthenium fresh leaves and plant s were air - dried for one week in the greenhouse. The cut samples (4 - 6 cm) were further dried in an electric oven at 70 ° C for 3 days. The oven - dried plant samples were then cut into smaller pieces (0.5 - 1 cm) and mixed with field soil. Four concentrations o f weed debris (e.g. 0, 0. 25, 0.5 and 1.0 g dry weight per 100g soil) were included. Twenty five non - dormant seeds of rice were put on the soil surface of pots. The pots were watered regularly with equal amount of water. The number of emerged seedlings was counted daily up to 12 days of seed placement. Plant height, leaf numbers and leaf area of rice were measured after 30 days of seed placement. The dry weight of randomly selected 10 seedlings was recorded after being dried at 72 ° C in an electric oven for seven days. The weed debris at different concentrations of Parthenium reduced the seed emergence, plant height, leaf numbers, leaf area and seedling dry weight of rice. Seedling emergence, plant height, leaf numb er, leaf area, and dry weight were reduced b y 25.40%, 20.98%, 20.02%, 33.85% and 22.78% respectively. Among all the parameters were considered, leaf area was most affected than other parameters. The inhibitory effects on rice were positively related to the concentratio n of parthenium weed debris in soil